Life Transformation in The Absolutely True Diary of A Part-Time Indian (2007) By Sherman Alexie - Rahman, Aulia; Al-Hafizh, Muhd. (Universitas Negeri Padang, 2021)
The aim of this study to find out how far Sherman Alexie’s novel The Absolutely True Diary of a-Part Time Indian (2007) bring ups and reveals the issue of life transformation which is done by the main character in this novel. It is intended also to find out how the fictional devices; plot (conflict) and setting in the novel give contribution in showing the meaning of life transformation. The result shows that the novel has represented the Indian’s life by portraying Indian as a poor, an alcoholic, and unwell educated tribe. The writer also finds out another positive side of Indian through the main character who showed in the novel. The common stereotype of Indian is not reflected by an Indian teenager who bring a hope for the future of Indian.